Diagnosis and Management of Chronic Kidney Disease-Mineral Bone Disease in Children - Jin-Soon Suh (Korean Society of Pediatric Nephrology, 2020)
Chronic kidney disease-mineral bone disorder (CKD-MBD) is a systemic disorder of mineral and bone metabolism caused by CKD. Patients with early-stage CKD who present with disordered regulation of bone and mineral metabolism may be asymptomatic. However, if untreated, the condition can be a significant barrier in achieving optimal bone strength, linear growth, and cardiovascular health in pediatric patients with CKD. Thus, the current study evaluated the definition, pathogenesis, diagnosis, and management of pediatric CKD-MBD.